Safety and Efficacy of Endovascular Treatment for Progressive Stroke in Patients With Acute Basilar Artery Occlusion - Wang, Yinxu; Ke, Yingbing; Wang, Lingling; Wu, Qing; Zhou, Jing; Tan, Xiaolin; Liu, Jiazuo; Geng, Wanjie; Cheng, Daoyou; Liu, Zongtao; Yu, Yinquan; Song, Jiaxing; et al. (Frontiers in Neurology, 2021)
Background and Purpose: It is unknown the benefit of endovascular therapy (EVT) for progressive stroke in patients with basilar artery occlusion (BAO). The aim of this study was to compare the efficacy and safety of EVT with standard medical therapy (SMT) in a population of BAO patients with progressive stroke. Methods: BASILAR is a prospective national registry of consecutive patients with acute BAO within 24 hours of symptom onset. According to the applied therapy, all patients were divided into SMT and EVT groups. Subsequently, the EVT group was divided into early (≤6h) and late groups (>6h) according to the time window. The efficacy outcome was favorable functional outcomes (modified Rankin Scale score≤3) at 90 days. The safety outcomes included mortality within 90 days and symptomatic intracerebral hemorrhage (sICH) after EVT. Results: The EVT cohort presented more frequently with a favorable functional outcome (adjusted odds ratio, 5.49; 95% confidence interval, 2.06-14.61, p = 0.01) and with a decreased mortality (adjusted odds ratio, 0.3; 95% confidence interval, 0.17-0.54, p < 0.001). What’s more, EVT still safe (P = 0.584, P = 0.492, respevticely) and effective (P = 0.05) in patients with progressive stroke when the treatment time window exceeds 6 hours. Conclusions: EVT was more effective and safer than SMT for progressive stroke in patients with BAO. Besides, EVT remains safe and effective in patients with progressive stroke when the treatment time window exceeds 6 hours. Predictors of desirable outcome in progressive stroke patients undergoing EVT included lower baseline NIHSS score, higher Baseline pc-ASPECTs, successful recanalization and shorter puncture to recanalization time.